A Multidimensional Approach to Assessing the Leverage Factors of the Sustainability of Seaweed Farming in Coastal Area of Parigi Moutong District, Indonesia - Alimudin Laapo; Dafina Howara; Saharia Kassa; Hardianti Sultan; Abd. Rahim (Journal of Aquaculture and Fish Health, 2021)
The sustainability of seaweed cultivation is influenced by multidimensional factors such as the quality of the aquatic environment, cultivation technology, economic contribution to cultivators, social conditions of the community, and government institutional support. This paper aims to reveal the leveraging factors for the sustainability of seaweed cultivation in the coastal area of Parigi Moutong Regency by using a multidimensional scaling approach and the RAPFISH application. The results showed that the sustainability of seaweed cultivation in the coastal area of Parigi Moutong Regency was in the less sustainable category. Leveraging factors that play an important role in the sustainability of seaweed farming are employment at the cultivator level and the feasibility of cultivation as a good factor, while the low quality of seeds of seaweed, socio-cultural capital, and fluctuating commodities prices are categorized as bad factors.